Pelatihan Pembuatan Minuman Sehat Berbahan Dasar Gula di Desa Lamondape Kolaka - Anti Landu; Asni; Bustang (TENANG : Teknologi, Edukasi, dan Pengabdian Multidisiplin Nusantara Gemilang, 2024)
A training session on the preparation of healthy beverages with palm sugar was held in Lamondape Village, Kolaka Regency, aimed at improving community knowledge, skills, and preparedness in leveraging local resources. The program had four primary sessions: an overview of the advantages and market potential of palm sugar, practical workshops on crafting nutritious beverages, approaches for packaging and branding, along with debates and a question-and-answer segment. The evaluation results indicate that most participants rated the training materials and delivery well, demonstrating the success of their preparation and presentation. Moreover, the training effectively enhanced participants' skills; nonetheless, some participants conveyed a deficiency in confidence regarding the application of the skills acquired. These findings underscore the necessity for further assistance in skill application and company advancement related to palm sugar. This training program positively influenced innovation and empowered the community by optimizing local resources